(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2025)
This article explores the issues of interaction between Kazakhstan and the United States in the field of technology transfer, considering the key challenges and prospects of this interaction. In the context of globalization and the rapid development of technology, effective transfer of knowledge and innovation is becoming an important factor for economic growth and modernization of Kazakhstan. The article examines the main aspects of the process of "transfer of technology and related rights from one side to another for their implementation and use" in Kazakhstan’s diplomacy, as well as the contribution of this process to international initiatives for their implementation and promotion at the global level. The author examines existing coordination mechanisms as shared scientific research, trade-off programs, investment undertakings and highlight main limitations such as legislative disparities, cultural obstacles and absence of infrastructure. The article also studies many problems regarding effective global cooperation in technology transfer sphere. Then the article raises the issue of effective expanding of cooperation between various organizations and nations to bring high level exchange of knowledge, information, know-how, and innovations. The article offers recommendations for improving cooperation, emphasizing the need for strategic planning and creating an enabling environment for innovation, which will allow both countries to maximize the benefits of partnership. Keywords: technology transfer, technological development, innovation, intellectual property, sustainable economic growth, diplomacy, international initiatives.